Opowieści o brzmieniu – o stylu i retoryce w opisach sprzętu audio na łamach czasopisma „Hi-Fi i Muzyka” - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper is dedicated to Hi-Fi magazines. The author offers a stylistic analysis of selected texts taken from “Hi-FI i Muzyka” (magazines from the 2012-2014 period), focused on specific types of columns: tests of audio equipment (amplifiers, CD players, gramophones, loudspeakers, etc). The article contains a short description of the magazine and its content, then author has suggested stylistic tools for describing sound (ordered in categories) and offered an analysis with citations.